PERLINDUNGAN KONSUMEN DALAM KEGIATAN TRANSAKSI JUAL BELI ONLINE DI INDONESIA - Riawan, Belly; Mahartayasa, I Made (Kertha Semaya : Journal Ilmu Hukum, 2015)
Along with the development of technology in the present, a lot of progress in allfields, especially in information technology. It was certainly used by Indonesian people fora variety of needs. One is in terms of buying and selling online. Then the transactionactivity of online media, because it is necessary at this time we also consider the legalaspects, especially the rights and obligations of both parties is assured. In the transactionprocess tends consumers feel insecure when melakukakan the process. Plus the validity of atransaction process according to Code of Civil Law (Civil Code) in 1458 as the referencesection of a transaction agreement. Because this activity is likely to lead to legal issues oneof which is fraud and selling online businesses. By using the method of the normative legalresearch. It can be concluded that legislation to date that can provide protection to theconsumer online transactions is Law No. 8 of 1999 on Consumer Protection in Section 8and Article 16.
Keywords: online transactions, fraud, protection, consumer